Rapid evidence profile #57: Examining the use of psychedelic-assisted psychotherapy for Veterans - Waddell, K; Velez, CM; DeMaio, P; Jaspal, A; Wilson, MG (My University, 2023)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about the use of psychedelic-assisted psychotherapy for Veterans in response to a decision-maker’s request.
Keywords: psychedelic; psychotherapy; Veterans